ANALISIS TINGKAT DISIPLIN KERJA KARYAWAN PADA TOKO SENJA KOSMETIK - Tsania , Syita; Suroso, Suroso; Karnama, Maman Mulya (Politeknik Negeri Ambon, 2023)
The purpose of this study was to determine the Compliance Level of Employee Discipline at Senja Cosmetics Shop and the factors that cause violations of employee work discipline. The research method used in this work uses a qualitative descriptive method. With this approach, the researcher wants to conduct research in a natural setting or following the existing context. The researcher leads according to the facts related to the Analysis of Employee Discipline Compliance Level at the Senja Cosmetics Shop. The results of the study show that the enforcement of work discipline at the Senja Cosmetics Shop is still said to be not good because there is no supervision of employees at the Senja Cosmetics Shop so there are still some employees who are undisciplined and the factors that cause violations of employee work discipline because there is no application of applicable sanctions and no definite rules or enforcement of written rules that can be used as a guide by employees at the Senja Cosmetics Shop. Leaders should need to supervise and take strict disciplinary action against employees so that employees can further improve their discipline.